2019
DOI: 10.1128/jvi.00338-19
|View full text |Cite
|
Sign up to set email alerts
|

Unique Interferon Pathway Regulation by the Andes Virus Nucleocapsid Protein Is Conferred by Phosphorylation of Serine 386

Abstract: Andes virus (ANDV) causes hantavirus pulmonary syndrome (HPS) and is the only hantavirus shown to spread person to person and cause a highly lethal HPS-like disease in Syrian hamsters. The unique ability of ANDV N protein to inhibit beta interferon (IFN␤) induction may contribute to its virulence and spread. Here we analyzed IFN␤ regulation by ANDV N protein substituted with divergent residues from the nearly identical Maporal virus (MAPV) N protein. We found that MAPV N fails to inhibit IFN␤ signaling and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 92 publications
(127 reference statements)
2
16
1
Order By: Relevance
“…Consistent with prior studies (53) , we observed a partial decline in RhoA binding to the phosphomimetic RhoGDI S34D mutant in the absence of ANDV N protein ( Fig 7A) and we found no difference in ANDV N protein binding to RhoGDI phosphorylation site mutants (Fig. 7B) (71) . However, we found no difference in the binding of RhoGDI to WT or ANDV N protein S386A/D/H mutants (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with prior studies (53) , we observed a partial decline in RhoA binding to the phosphomimetic RhoGDI S34D mutant in the absence of ANDV N protein ( Fig 7A) and we found no difference in ANDV N protein binding to RhoGDI phosphorylation site mutants (Fig. 7B) (71) . However, we found no difference in the binding of RhoGDI to WT or ANDV N protein S386A/D/H mutants (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…cAMP activated protein kinase A (PKA) directs RhoGDI-S174 phosphorylation which stabilizes RhoGDI binding to Rho family kinases and could impact N protein binding to RhoGDI (51,52,54,61,64,65,(74)(75)(76)(77)(78) . In addition, ANDV N protein is phosphorylated on S386 (71) , and the phosphorylation of ANDV N protein could impact its binding to RhoGDI or PKA directed phosphorylation of RhoGDI. We expressed S386A, S386D and S386H mutants of ANDV N protein and determined if mutant N proteins bind to RhoGDI or alter RhoGDI-S174 phosphorylation.…”
Section: Andv N Protein Phosphorylation Does Not Impact Rhogdi Bindinmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that SEOV infection of macrophages and lymphocytes could reduce the immune response and thus contribute to persistent infection [71]. Although the A129 mice used in our study had abrogated type I IFN receptors, it is surprising that the uncoupling of the IFN response pathway was not enough to lead to disease, as hantaviruses have evolved mechanisms to inhibit production of type I IFN upon infection [72,73]. Thus our data suggest that other pathways must be disengaged in order to exert virulence.…”
Section: Discussionmentioning
confidence: 78%
“…Syrian hamsters are tolerant to certain hantaviruses, such as Sin Nombre Virus (SNV), but succumb to the closely related Andes Virus (ANDV), with symptoms remarkably similar to the human manifestation of the disease [ 59 , 60 , 61 ]. Although comparative analyses are scarce, ANDV appears to avoid early innate immune recognition and elicit a stronger immune response later on [ 59 , 62 ]. Priming with poly I:C or SNV protects hamsters from ANDV-driven pulmonary disease, suggesting that rapid IFN responses may allow for viral control while avoiding later immunopathology [ 63 ], similar to bats.…”
Section: Innate Immunity In Reservoirs Of Zoonotic Virusesmentioning
confidence: 99%